(untitled) (World Bulletin of Management and Law, 2025)
The rapid digital transformation of the global economy has reshaped trade, investment, and foreign economic policy. For emerging economies such as Uzbekistan, the integration of e-commerce and digital platforms into foreign economic strategy presents both opportunities and challenges. This article investigates the strategic directions for embedding digital trade within Uzbekistan’s external economic policy. Using a policy analysis framework supported by comparative review and strategic assessment tools, the study evaluates Uzbekistan’s institutional reforms, legal frameworks, and ecommerce growth trajectory. It further benchmarks Uzbekistan’s progress against international experiences in Kazakhstan, Vietnam, and China. The findings reveal that Uzbekistan has demonstrated rapid e-commerce expansion, increasing ICT contributions to GDP, and notable institutional reforms under the Digital Uzbekistan 2030 strategy. However, persistent challenges remain, including low SME adoption, limited cross-border integration, and regulatory constraints. The paper argues that Uzbekistan can leverage digital platforms not only to boost trade facilitation and export diversification but also to position itself as a regional hub for digital commerce. Policy recommendations include regulatory harmonization, enhanced SME capacity-building, investment in digital infrastructure, and alignment with WTO and EEU frameworks. By strategically integrating e-commerce into foreign economic policy, Uzbekistan can accelerate its transition toward a more resilient and globally competitive digital economy.